Pengaruh Investasi Dan Pengeluaran Pemerintah Terhadap Pendapatan Asli Daerah Di Provinsi Sumatera Utara - Husna, Wardatul; Juanda, Reza; Saharuddin, Saharuddin; Murtala, Murtala (LPPM UNIMAL, 2024)
This research aims to determine the influence of government investment and expenditure and local revenue in the province of North Sumatra. The data used in this research uses the multiple linear regression analysis method using the E-views 10 program. The partial research results show that the investment variable has a negative and significant effect on local revenue, the government expenditure variable has a positive and significant effect on local revenue, research results Simultaneously, investment and government expenditure variables have a significant effect on local original income. The Determination Coefficient (R2) is 0.667388. This means that the magnitude of the influence of investment variables and government expenditure on the local income of North Sumatra Province is 0.6674 (66.74%) while that which is influenced by other variables outside this research model is 0.3326 (33.26%).